Impact of Buddhism as a Cult in Ancient Kamarupa: A Historical Study (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Buddhism is a philosophy and religion that originated in India in the late 6th century BCE. In 6th century BC some religious movement began to protect society from the domination of priesthood and socio-religious unrest and it was during this time that Buddhism was born in India. Through Buddhism, Gautam Buddha, the founder of Buddhism propagated the message of enlightenment to people. Buddhism has a significant contribution to the Indian culture and civilization. Since very ancient time various religious beliefs existed in ancient Kamarupa and gradually Buddhism made its way in Kamarupa. As Brahmanical religion was to some extent strong in ancient Kamarupa, so Buddhism could not settle in this land easily. Historical evidences tell us about the Brahmanical culture of ancient Kamrupa. But different sources tell us about the development of Buddhism in ancient Kamarupa. In this paper an attempt has been made to throw a light on the development of Buddhism in ancient Kamarupa and its impact in society.